PENERAPAN KONSEP LITERASI DASAR DALAM PEMBELAJARAN BAHASA ANAK USIA DINI DI RA USWATUN HASANA PAJARAKAN-PROBOLINGGO - Terza Travelancya dp (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2022)
Literacy is learning that emphasizes language that focuses on the needs of children's vocabulary development when speaking. The purpose of the study was to describe the application of literacy in children's language learning at RA Uswatun Hasanah. The research method used is descriptive-qualitative with the type of case study research on children's language skills. The results of the study include teachers applying RPPH appropriately in children's language learning, utilizing language learning when children are able to increase new vocabulary and choosing methods that are appropriate to the child's developmental stage. Then, the supporting factors include language strengthening tools through the media, and the use of storytelling methods related to children being able to compose words so that one sentence. The inhibiting factor is related to the lack of facilities and the habit of applying literacy which is assisted by parents when children study at home. Suggestions for research in developing literacy in children's language through choosing the method of children's language skills. Then, the learning process is carried out repeatedly.